Sharia Economic Literacy for Islamic Education Students at STAI Asy-Syukriyyah: Literature Study on Prevention of Online Gambling and Illegal Online Loans - Muchtar, Evan Hamzah (YASIN, 2025)
This research employs a qualitative literature study approach to investigate the critical need for Islamic economic literacy as a deterrent against students' engagement in online gambling and illegal online loans. Through classroom observations and content analysis of secondary sources, including journals, news articles, and curriculum documents, three primary findings emerged: (1) a limited understanding of the application of Islamic principles in digital transactions, (2) the aggressive marketing tactics of non-Islamic platforms that exploit students' financial vulnerabilities, and (3) a significant disconnect between the muamalah fiqh curriculum and the actual financial behaviors of students. To address these issues, this study proposes an implementation framework that includes enriching the curriculum with relevant case studies, establishing a student literacy ambassador program, and fostering collaboration with Islamic financial authorities. These findings contribute to the discourse on developing Islamic economic education that effectively responds to contemporary digital challenges, particularly in enhancing the financial resilience of the young Muslim generation.